Political Places in Everyday Usage: Finding Alternatives for Memory in the Birthplace of Josip Broz Tito - Škrbić Alempijević, Nevena (2008)
This paper analyzes the ways in which the inhabitants of Kumrovec, the birthplace of Yugoslavia’ s president-for-life, come to terms with, negotiate or even subvert the dominant narratives about their home-village. In public discourse Kumrovec is still known as a symbolic "cradle" of socialist ideology. Components of the socialist built environment, erected between the 1950s and 1980s, are used as proof that "the place still remembers". This makes Kumrovec a cast-study of the post-Yugoslav transition story, that is, a place burdened by its past. Previous studies of Kumrovec focused on the politicization of the place during socialism and the subsequent "social amnesia" to which it was subjected in the 1990s. In these studies the place is featured as "contested territory" where two conflicting ideologies and memory systems collide. These accounts depict the "locals" as passive, bending under the political pressures placed upon them. This paper seeks to move beyond such passive representations. Based on ethnographic fieldwork conducted in Kumrovec between 2004 and 2008, I explore some notions from the anthropology of space and place to ask how people actually lived in and related to the village’ s politics of place. I attempt to move away from the perception of culture as a text and focus more on what people do in this setting. Does Kumrovec function as a “ political” place in their everyday practices? Is their wish to find new interpretations for the socialist architecture past- or future-oriented? I approach these individuals as active agents making sense of the place's past and designing its futures in their own unrepeatable ways.